(untitled) (Revista Educação, Artes e Inclusão, 2025)
The present study permeates the discussions regarding the treatment of dance in the school environment, focusing on the dances present in the popular culture of the northeast, more precisely in the state of Pernambuco. This study is justified from the guidelines proposed by the Curriculum of Pernambuco that establish regional dances as a content of School Physical Education. This discussion aims to investigate the limitations and possibilities for dealing with Northeastern dance in Physical Education classes at school. From there, to establish reflections on the relevance of valuing the local culture in the formation of historical subjects from the appropriation of the body culture of movement. The design of this article is characterized as a qualitative narrative literature review. It was possible to verify that the access to the systematized knowledge of dance enables the production of new knowledge of social practice and it was concluded that the regional manifestations collaborate in the formation of the student from their socio-historical and cultural legacy.